Mobility Of The Future - Malzfeldt, Linus; Ryška, Tomáš, 1976-; Sieber, Patrik, 1977-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
The mobility of the future should not only provide the best possible customer experience but also be sustainable. An industry that knew only the direction of growth for decades, the aviation sector, is currently experiencing its most severe crisis. The social acceptance of short-haul flights has already decreased before. Hence, this crisis might be the ideal chance for companies in this industry to develop into a general mobility provider that aligns the previously described goals in one solution. This master thesis will examine if an intermodal rail and aviation model can do so and if both means of transportation can be combined more efficiently. The outcome should consult airlines concerning this strategic decision. A combination of an academic literature review and qualitative interviews with company representatives was chosen for the research approach. The practical examples revealed that substitution of short-haul flights by other transport means, particularly high-speed trains, can be recommended. Not only sustainability potentials arise from such a cooperation, but also economic ones. However, the reports also highlighted difficulties in implementation and a variety of requirements. The outlook on the mobility of the future suggests the relevance of an intermodal strategy that focuses on building an open transportation eco-system rather than integrating single providers.
Vedoucí práce: Tomáš Ryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses